Analisis Wisata Dalam Meningkatkan Pendapatan Pemerintah Desa dan Ekonomi Masyarakat Desa Cisantana - Didik Hadiyatno (CV. Kalimasada Group, 2023)
As an effort to face various challenges and developments in the situation, both at home and abroad, the Unitary State of the Republic of Indonesia (NKRI) made fundamental changes by giving broad, real and responsible authority to the regions proportionallyThe purpose of this study is to find out how the role of Sukageri View tourism in increasing Village Government Revenue and the welfare of the people of Cisantana Village, and what are the strengths, weaknesses, opportunities, and threats of Sukageri View tourism. The research method uses a qualitative approach by presenting data in the form of descriptions. Data was collected through in-depth interviews with informants, including the Cisantana Village Government, local Cisantana Village communities, tourism managers, and visitors. The results showed that the existence of Sukageri View tourism was able to play a role in increasing the Original Income of the Village Government and the welfare of the people of Cisantana Village. This is evidenced by the increasing income from the tourism sector and awareness of education from the public and increasing people's purchasing power. The main strengths of this tourism are natural beauty, dry land weakness, tourism opportunities with the concept of ecotourism, and the threat of new tourism presence in Cisantana Village